EXECUTIVE LEADERSHIP AND ADMINISTRATIVE MANAGEMENT OF PUBLIC EDUCATIONAL INSTITUTIONS AT THE INITIAL LEVEL UGEL 01 IN LIMA - Ruiz Cutipa, Verónica Violeta (2020)
The research addressed the variables,managerial leadership and administrativemanagement with the purpose of showing thelevel of relationship between each other in theteachers of the initial level of RED 19 UGEL 01,Villa el Salvador-Lima. Having hypothesized, thereis a direct relationship between variables. By itsnature, the research is basic, descriptive designand correlational level, quantitative approach. Thesample was made up of 102 initial level teachers.The information was collected using the escalationtechnique, the instrument was the Likert scale with24 items for both variables. The data were processedin tables and figures, the hypothesis was tested,obtaining a value of r = 0.895, p-value <0.05 for thegeneral hypothesis. The conclusions allowed us toaffirm that there is a relationship between managerialleadership and administrative management in publiceducational institutions of the initial level RED 19UGEL 01, Villa el Salvador-Lima 2019. The betterthe managerial leadership, the better the educationalmanagement.